ABOUT DIGITAL MOCK-UP FOR MECHANICAL PRODUCTS - GHERGHINA George; TUTUNEA Dragos; POPA Dragos (Journal of Industrial Design and Engineering Graphics, 2015)
The development of contemporary society made the tools and methods CAD CAM CAE have increasingly more applications. The paper presents same aspects of composition of digital mock-up and the requirements of a digital mock-up model. Digital mock-up design allows engineers to design, to model complex structures and verify the design of a product without ever needing the achieved physically real construction. This makes possible a number of advantages such a: • Reduce time to market by identifying problems at the design. • reduce production costs by minimizing the number of prototypes to be made. • improving product quality by allocating alternative project to be verified before the final one to be elected. • division of responsibilities regarding product functions within the enterprise. The digital mock-up of the product is built at a design stage, and is applicable to the whole life-cycle of the product, including design, manufacture, marketing and aftermarket. The digital mock-up could achieve interference check, motion analysis, simulation of performance and manufacturing, technical training, advertising and maintenance, planning etc. The DMU of mechanical products, as important engineering data in a company, is supposed to be able to support all the activities in the whole life-cycle of the product including design, manufacture, marketing and aftermarket